1998
DOI: 10.1159/000015091
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of DUSP6, a dual specificity MAP kinase phosphatase, in pancreatic cancer

Abstract: DUSP6 (alias PYST1), one of the dual-specificity tyrosine phosphatases, is localized on 12q21, one of the regions of frequent allelic loss in pancreatic cancer. This gene is composed of three exons, and two forms of alternatively spliced transcripts are ubiquitously expressed. Although no mutations were observed in 26 pancreatic cancer cell lines, reduced expressions of the full-length transcripts were observed in some cell lines, which may suggest some role for DUSP6 in pancreatic carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 10 publications
3
50
0
Order By: Relevance
“…The possible relevance of these gene expression changes to tumorigenesis is further underlined by the fact that the expression of more than one-third (7/19) of the genes that are suppressed by telomerase is suppressed in murine and human tumors as well as in a variety of tumor-derived cell lines. Such putative tumor suppressor genes include Bhlhb2 (Collado et al, 2005), Dusp6 (Furukawa et al, 1998(Furukawa et al, , 2003, Gadd45b (Hu et al, 2004), Gadd45g (Zhang et al, 2002;Chung et al, 2003;Sun et al, 2003), JunB (Hu et al, 2004), Klf4 (Wang et al, 2002;Ohnishi et al, 2003;Zhao et al, 2004;Rowland et al, 2005;Wei et al, 2005), and Tieg1 (Reinholz et al, 2004), Taken together, these data suggest that the transcriptional response to increased telomerase activity creates a cellular context that favors proliferation and tumorigenesis. Interestingly, the majority of mTert-suppressed growth inhibitory genes are downstream targets of TGF-b (see Figure 3a and Supplementary Table), suggesting that increased mTert expression interferes with TGF-b signaling.…”
Section: Discussionmentioning
confidence: 86%
“…The possible relevance of these gene expression changes to tumorigenesis is further underlined by the fact that the expression of more than one-third (7/19) of the genes that are suppressed by telomerase is suppressed in murine and human tumors as well as in a variety of tumor-derived cell lines. Such putative tumor suppressor genes include Bhlhb2 (Collado et al, 2005), Dusp6 (Furukawa et al, 1998(Furukawa et al, , 2003, Gadd45b (Hu et al, 2004), Gadd45g (Zhang et al, 2002;Chung et al, 2003;Sun et al, 2003), JunB (Hu et al, 2004), Klf4 (Wang et al, 2002;Ohnishi et al, 2003;Zhao et al, 2004;Rowland et al, 2005;Wei et al, 2005), and Tieg1 (Reinholz et al, 2004), Taken together, these data suggest that the transcriptional response to increased telomerase activity creates a cellular context that favors proliferation and tumorigenesis. Interestingly, the majority of mTert-suppressed growth inhibitory genes are downstream targets of TGF-b (see Figure 3a and Supplementary Table), suggesting that increased mTert expression interferes with TGF-b signaling.…”
Section: Discussionmentioning
confidence: 86%
“…Elevated DUSP6 transcript levels have been reported as a risk factor for poor prognosis in non-small cell lung cancer patients [21] and tamoxifen resistance in breast cancer patients [43] . In contrast, DUSP6 is a candidate tumor suppressor gene in pancreatic cancer [42] and primary human ovarian cancer cells. CPEB4 binds to the cytoplasmic polyadenylation element (CPE) of target mRNAs and [14] ; Model 3: Five selected genes of Han et al [15] ; B: Logistic regression coefficient beta; SE: Standard error of B; P: P value with statistical significance; H-L: Hosmer and Lemeshow test P value R2: Nagelkerke R Square; AUC: Area under ROC.…”
Section: Discussionmentioning
confidence: 98%
“…Higher MDM2 expression has been reported in a variety of human stromal and epithelial malignancies, including colorectal cancers [33][34][35][36][37][38] . DUSP6, also known as MAPK phosphatase 3 (MKP3), inactivates MAPK1/ERK2 [39][40][41][42] . Elevated DUSP6 transcript levels have been reported as a risk factor for poor prognosis in non-small cell lung cancer patients [21] and tamoxifen resistance in breast cancer patients [43] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the MKP-1 phosphatase is overexpressed during the early phases of human epithelial carcinogenesis and could therefore act as a marker for a wide range of tumours (Loda et al, 1996;Magi-Galluzi et al, 1997;Yokoyama et al, 1997). In contrast, analysis of the levels of PYST1/MKP-3 in pancreatic cancer cell lines revealed reduced expression of this phosphatase in some of these cell lines suggesting a role of PYST1 in pancreatic carcinogenesis (Furukawa et al, 1998). Deletions of human chromosome 1q32, the region to which MKP5 localizes, have been reported in renal collecting duct carcinoma (CDC) and some breast tumours (Steiner et al, 1996;Benitez et al, 1997).…”
Section: Chromosomal Location Of the Mkp5 Genementioning
confidence: 99%